Expressive Speech Acts Analysis of “Looking for Alaska” Novel by John Green - Galuh Virginia Elhamsyah; Ambalagin, Ambalegin (IdeBahasa, 2023)
This descriptive qualitative research discovered the expressive acts in John Green's novel "Looking for Alaska.". Martinez's (2013) theory was used to analyze the types of expressive acts that found in the data source. The data for this research was collected by using an observational method and a non-participation technique. Then, the data was analyzed using the pragmatic identity method and pragmatic competence in equalizing. The researchers identified in 20 utterances that uttered by the characters in the novel. The utterances consisted of 5 types of commissive acts. Those types were four data of the expression of thanking, five data of the expression of apologizing, two data of the expression of boasting, and three data of the expression of condoling. Additionally, among those types of expressive acts, boasting became into the most prominent types that appeared in the data source.